Assembling Ultrafine SnO2 Nanoparticles on MIL-101(Cr) Octahedrons for Efficient Fuel Photocatalytic Denitrification - Ruowen Liang; Shihui Wang; Yi Lu; Guiyang Yan; Zhoujun He; Yuzhou Xia; Zhiyu Liang; Ling Wu (Molecules, 2021)
Effectively reducing the concentration of nitrogen-containing compounds (NCCs) remains a significant but challenging task in environmental restoration. In this work, a novel step-scheme (S-scheme) SnO2@MCr heterojunction was successfully fabricated via a facile hydrothermal method. At this heterojunction, MIL-101(Cr) octahedrons are decorated with highly dispersed SnO2 quantum dots (QDs, approximate size 3 nm). The QDs are evenly wrapped around the MIL-101(Cr), forming an intriguing zero-dimensional/three-dimensional (0D/3D) S-scheme heterostructure. Under simulated sunlight irradiation (280 nm < λ < 980 nm), SnO2@MCr demonstrated superior photoactivity toward the denitrification of pyridine, a typical NCC. The adsorption capacity and adsorption site of SnO2@MCr were also investigated. Tests using 20%SnO2@MCr exhibited much higher activity than that of pure SnO2 and MIL-101(Cr); the reduction ratio of Cr(VI) is rapidly increased to 95% after sunlight irradiation for 4 h. The improvement in the photocatalytic activity is attributed to (i) the high dispersion of SnO2 QDs, (ii) the binding of the rich adsorption sites with pyridine molecules, and (iii) the formation of the S-scheme heterojunction between SnO2 and MIL-101(Cr). Finally, the photocatalytic mechanism of pyridine was elucidated, and the possible intermediate products and degradation pathways were discussed.